Answer:
(-1, 1)
Step-by-step explanation:
Midpoint formula: (x₁ + x₂/2 , y₁ + y₂/2)
Substitute the values into the formula.
(-5 + 3/2 , 3 - 1/2)
(-2/2 , 2/2)
(-1,1)
Therefore, the midpoint is (-1, 1).
Answer:
7×11=77
Step-by-step explanation:
7
9+2=11
7×11=77
Factor out the trinomial. Find factors of x² and 6 that would, when added, give you 5x
x² = x * x
6 = 3 * 2
(x + 3)(x + 2) are your binomials.
To solve for x, set each parenthesis = 0
x + 3 = 0
x + 3 (-3) = 0 (-3)
x = -3
x + 2 = 0
x + 2 (-2) = 0 (-2)
x = -2
x = -3, -2
hope this helps